PERANCANGAN ALAT PENANAM BENIH JAGUNG DAN PENYIRAMAN - Togar P.O. Sianipar; Zulkarnain Fatoni (Jurnal Turbulen, 2019)
From year to year the need for Indonesian corn continues to increase in the field of agriculture equipment sector must continue to be developed and continue to innovate to achieve maximum productivity, one of which is a tool of corn seeds Existing seeds must also be developed, the existing seed planter is limited only to do the planting of seeds without any excess on the tools designed planting tools corn seeds added with watering system, can be concluded The function of corn seed planter is to do seed planting and to do watering using one tool, the maximum capacity of watering for this tool is 5 liters and watering for one hole planting is 200 ml.  Keywords: : Seed  planting tools, corn seeds, watering tools